Acoso psicológico y el desarrollo de la identidad en los estudiantes de la Unidad Educativa 24 de Mayo año 2019 - Sinchiguano Chango, Juan Carlos (2019)
Psychological harassment is defined as any act that lowers the self-esteem of children and adolescents or blocks children's interaction initiatives, by adult members of the family group, It is characterized both by manifestations that are a consequence of active behaviors (reject , ignore, isolate, terrorize) as by behaviors of omission (deprivation of feelings of love, affection or security) ”. For this reason psychological harassment is also considered “chronic verbal hostility in the form of insult, contempt, criticism or threat of abandonment, and constant blocking of psychological interaction initiatives is (from avoidance to confinement or confinement) by any adult member of the family, social and educational group. It is for this reason that this research work was carried out in the Educational Unit "May 24" of Canton Quevedo to establish that psychological harassment influences the development of the emotional identity of adolescents, in addition to publicizing the causes of family dysfunction and the types of aggressive behavior that adolescent’s exhibit. At the time of applying the respective surveys to the students in the aforementioned institution, important data were obtained on the psychological harassment that adolescents present, after tabulating each of the surveys the necessary information was obtained to reach the sustainable conclusion and power Provide the respective recommendations for the benefit of the students of the “May 24” educational unit.